Analisis Cognitive Misers Theory dalam Penggunaan Artificial Intelligence serta Dampaknya terhadap Kemalasan Kognitif Siswa Madrasah Aliyah Negeri di Kabupaten Lamongan - Evi Wiyanti; Nabillah Syah Putry (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This study aims to analyze: (1) the forms of Artificial Intelligence (AI) usage as a shortcut thinking tool among students of Madrasah Aliyah Negeri in Lamongan Regency, (2) the use of AI from the perspective of Cognitive Misers Theory, and (3) its impact on students’ cognitive laziness. This research employs a qualitative approach using a case study method to gain an in-depth understanding of students’ behaviors, experiences, and thought patterns within the context of digital learning culture. The participants consisted of 30 students from Madrasah Aliyah Negeri in Lamongan Regency, selected through purposive sampling based on the intensity of their AI usage in academic activities. Data were collected through semi-structured in-depth interviews, school documents, learning assignment patterns, and relevant literature. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that: (1) AI is used as a shortcut thinking tool to obtain quick answers, simplify difficult tasks, reduce cognitive burden, and accelerate task completion. This behavior is influenced by the school environment, social media, digital culture, and limited critical AI literacy; (2) from the perspective of Cognitive Misers Theory, students’ AI use reflects a tendency to conserve mental effort through cognitive offloading, shallow information processing, the use of instant heuristics, and a preference for practical solutions over deep understanding; and (3) the impacts include declining critical thinking skills, increasing dependence on AI, the strengthening of a pragmatic learning culture, weakened independent learning, and the normalization of an instant culture that may reinforce cognitive laziness. This study concludes that AI has shifted from being a learning support tool to an instrument of academic efficiency that risks transforming reflective learning into a pragmatic culture if not balanced with critical AI literacy and adequate pedagogical supervision.